Toward democratic victory. [By] M. Ezekiel, M. Bondfield, A. Meiklejohn a.o. Ed. by C. Ware and E. Doerfler (American Council on Public Affairs)
With appendix. Lectures given at the 10th annual conference of the Summer Institute for Social Progress at Wellesley, on July 4-10, 1942.